Effects of micron-sized Cr3Si particles on microstructure and properties of CuNiSiCr alloy - Zhongyue Yang; Yake Wu; Liang Zhou; Bai Li; Feng Jiang; Junyong Lu (Journal of Materials Research and Technology)
The microstructure evolution and properties of CuNiSi and CuNiSiCr alloys were systematically compared to understand the effects of micron-sized Cr3Si particles during thermomechanical processing. It was found that the Cr3Si particles complexified the structure of the deformation bands and induced particle deformation zones after cold rolling. These deformation heterogeneities increased the number of nucleation sites and resulted in more significant grain refinement in the CuNiSiCr alloy upon recrystallization. As for textures, the Cr3Si particles did not alter the components but weakened their intensities. Analysis of grain growth kinetics revealed that Cr3Si particles can hinder grain growth and even restrict the grain size to a fine scale, thus enhancing the grain size stability at high temperatures. After aging, the fine-grained CuNiSiCr alloy showed an elevated work hardening rate, improving the ultimate tensile strength and elongation. This study highlights the potential of using micron-sized particles to design high-performance copper alloys, offering valuable insights for applications in electrical and electronic industries.